Domestic & relational violence - McLeod, David Axlyn (Handbook of forensic social work, 2024)
No matter the name (domestic violence, intimate partner violence, relational violence), violence in relationships is epidemic in the United States, and social workers will be interacting with clients experiencing this. In all practice settings, and especially those directed toward it, these patterns of abuse and maltreatment in relationships are important for social workers to be able to identify and communicate about. Over the years multiple theoretical models have been used to explain the phenomenon, and this chapter will detail those as well as present social workers with a modernized conceptual model to understand and intervene in regards to physical, sexual, social, emotional, psychological, and other forms of violence in relationships.